DIFFERENTIATION OF TYPHUSS TRAINS BY SLIDE AGGLUTINATIVE TESTS - RUIZ CASTANEDA, MAXIMILIANO (HOSPITAL GENERAL, LABORATORIO DEL TIFO, CD. MEXICO, DF, MEX, 1966)
A slide-agglutinative test is described which simplifies studies on the determination of the type of typhus infection. The antigens are rich suspensions of murine and classic rickettsiae prepared from the lungs of mice intranasally infected with either ty
J IMMUNOL
Keywords: DIFFERENTIATION, TYPHUSS, TRAINS, SLIDE, AGGLUTINATIVE, TESTS; CIENCIAS MEDICAS; PATOLOGIA; TIFO